Electro‐Powerless Balloon Soft Actuator with Manually Driven Fluidic Circuit. (20th December 2022) - Matsuda, Ryosuke; Song, Zihao; Ota, Hiroki
Abstract: Balloon‐type actuators have attracted scientific attention because they allow easy control of the output intensity and a high degree‐of‐freedom regarding shape and movement. However, they require bulky external pumps and electric power suppliers. This makes miniaturization and wearable device fabrication difficult. Herein, a balloon soft actuator that does not require a pneumatic pump or electric power supplier, and that uses a finger‐operated pump based on a fluidic circuit and catalytic reaction, is proposed. This device can be driven without electric power multiple times by applying a vent valve system to exhaust the generated gas. Further, it is applied to two different types of applications—soft robots and wearable devices—by optimizing their structure and material. In conclusion, the proposed device is expected to lead to the development of a broad range of soft actuators for stand‐alone robots and wearable devices in the future. Abstract : An infusion system is fabricated by using a hand pump with a fluidic system. The implementation of a soft actuator that does not require external electric power and is manually driven by gas generation based on a chemical reaction is demonstrated. By using this system, a tentacle‐inspired soft gripper robot and a grasp‐assisting wearable device are fabricated.